Klik, Pilih, Makan: Mengungkap Determinan Niat untuk Membeli Makanan via GrabFood - Wulandari, Aline; Atmaja, Ferry Tema (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study aims to examine the effect of product presentation, food quality, and food safety optimism on intention to buy a food on the GrabFood application. The quantitative study collected data from 303 respondents through an online questionnaire with a Likert scale and using the help of TSurvey. The analysis technique employed the Structural Equation Modeling (SEM) method with the help of the SmartPLS application. The results showed product presentation and food quality had a positive and significant effect on food safety optimism, food quality had a positive and significant effect on intention to buy, and product presentation and food safety optimism had no significant effect on intention to buy. This study makes a theoretical contribution in expanding the understanding of the factors that influence consumer purchase intention and offers practical implications in designing effective marketing strategies through online food ordering applications.